Soft activism and corporate dividend policy: Evidence from institutional investors site visits - Cao, Jerry; Wang, Hanyang; Zhou, Sili (Journal of Corporate Finance, 2022)
We study the governance effect of institutional site visits and focus on corporate payout. Due to the weak investor protection and poor information quality in China, institutional investors resort to site visits as a form of soft activism. We show that site visits lead to an increase of corporate cash dividend, through the mechanism of disciplining management with exit threats. Such effect is more pronounced for visits by state-owned institutions. We further confirm the causal link with both difference-in-difference analysis and instrumental variable regression. The paper contributes to the research on soft activism and governance device of institutional investors in weak institutional environments.